1998
DOI: 10.1136/adc.79.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic exocrine and endocrine function after pancreatectomy for persistent hyperinsulinaemic hypoglycaemia of infancy

Abstract: Aim-To evaluate long term detailed pancreatic endocrine and exocrine function in children with persistent hyperinsulinaemic hypoglycaemia of infancy (PHHI) after 85-95% pancreatectomy. Methods-Six children with PHHI between 0.9 and 12.7 years after pancreatic resection underwent clinical and investigative follow up at 1.0 to 14.9 years of age. One child with PHHI who had not had pancreatectomy was also assessed. Standard endocrine assessment, pancreatic magnetic resonance imaging (MRI), and detailed direct and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
(19 reference statements)
0
22
0
3
Order By: Relevance
“…This risk increases with age, especially after puberty, and might also be even higher [62]. The exocrine pancreas function might be also altered after subtotal pancreatectomy but this is less frequent and not all patients require supplementation of pancreatic enzymes [15,28]. The ®nal decision for a radical surgical intervention in the diuse form has to be made very carefully and individually for each patient.…”
Section: Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…This risk increases with age, especially after puberty, and might also be even higher [62]. The exocrine pancreas function might be also altered after subtotal pancreatectomy but this is less frequent and not all patients require supplementation of pancreatic enzymes [15,28]. The ®nal decision for a radical surgical intervention in the diuse form has to be made very carefully and individually for each patient.…”
Section: Treatmentmentioning
confidence: 97%
“…Whereas in focal disease a limited resection of the focal area with preservation of as much pancreas as possible is performed, extension of surgery for diuse disease up to complete pancreatectomy results in an increasing risk of developing diabetes mellitus [15,62,69]. A recent study reported the occurrence of diabetes in 67% of patients after a >95% pancreatectomy [15].…”
Section: Treatmentmentioning
confidence: 98%
“…An improvement in adequate management will be achieved by the recently developed management recommendation by the ENRHI (European Network of Research in Hyperinsulinism) which proposes pancreatic venous sampling prior to surgery (4,15,23,24). If no focal lesion is found during this procedure and a diffuse disease is likely, long-term octreotide treatment has to be considered, especially since after near total pancreatectomy or recurrent operations the risk of developing insulindependent diabetes mellitus is known to be greatly increased, especially after puberty (11,12). At present, the overall incidence of insulin-dependent diabetes is about 27% for all operated patients after a mean follow-up period of 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is known that this might be due to the presence of overlooked focal lesions, especially localized in the head of the pancreas. Besides this, undirected extensive pancreatic resection is associated with a high risk of developing diabetes mellitus (11,12). An alternative drug for long-term treatment is long-acting somatostatin (octreotide) in addition to a carbohydrate-enriched diet and frequent feedings (13).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of these complications (in up to 50% of survivors) has changed little during the past 20 years which indicates the major problems that are faced in managing and treating this condition [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13]. In addition to genetic disorders, hyperinsulinism in infants can also be present as a transient condition (lasting 1–2 days, or several months) associated with maternal diabetes, rhesus incompatibility, perinatal stresses such as birth asphyxia, maternal toxaemia, or intrauterine growth retardation [14, 15, 16].…”
Section: Introductionmentioning
confidence: 99%